Social Media Influencers : Case Taiwan - Lin, Anne (2020)
This study looks at social media influence from the perspective of 3 Social Media Influencers (SMIs) in Taiwan. The purpose of the study is to provide a “behind-the-scenes” accounts of social media work strategy and career reflection from SMIs’ perspective. This is a qualitative research with a case study approach. The interviews were done through an online platform and video recorded. The data were analyzed with a thematic approach. The findings first included discussions of SMI social media strategies. The data also revealed SMI insights on creating influential content online. SMIs then provided personal views of current social media trends. Lastly, there were reflections on the challenges and lessons learned from the profession of SMI. The results show SMI emphasize on finding value at work. They aim to be authentic online and constantly evolve in their work. In addition to content specific advice, SMI provided many universal life values. Finally, spontaneity was a major element of SMI content creation.